The effectiveness of discharge planning and range of motion (ROM) training in increasing muscle strength of nonhemorrhagic stroke patients - Mohamat Iskandar (GHMJ (Global Health Management Journal), 2018)
Background: Non-hemorrhagic stroke patients experience hemiparesis, an improper handling results in joint contractures. Discharge planning combined with a range of motion (ROM) training given to patients and their families are expected to improve muscle strength in patients after returning from the hospital. Aims: This study is to identify the effectiveness of discharge planning in increasing muscle strength. Methods: This is a quasi-experimental study with a pre-posttest design. A total of 34 respondents were selected by cluster random sampling technique, from RAA Soewondo Pati General Hospital of Pati, Central Java, Indonesia. The respondents were divided equally into two groups; an intervention group (N = 17) was given a discharge planning program together with stroke information and range of motion (ROM) training while the control group (N = 17) received a standard discharge planning available in the hospital. Further, Muscle Rating Scale (MRS) was employed to assess the muscle strength on the 2nd, 7th, and 14th day after discharge planning presented to the nonhemorrhagic stroke patients. Results: This present study clearly acknowledges the standard discharge planning program available in the hospital improve the muscle strength of the upper and lower extremity in the nonhemorrhagic stroke patients just 2nd day after the care (pretest), and the significant improvement was observed until the day 14. Moreover, combining the care with ROM training at the intervention group faster the recovery and the muscle strength improved significantly at the 7th day and continue increase at the day 14. Looking to the muscle strength since the 2nd day to the day 14, respectively the muscle strength of upper and lower limb at the control group improved at the point of 0.588 and 0.882, while at the group received the ROM training reached the value of 1.472 and 1.412. Conclusions: The ROM training combined to the current discharge planning program will faster the muscle strength recovery of the nonhemorrhagic stroke patients. This research provide insight how family plays important role to the success in monitoring the rehabilitation and recovery progress.